2019
DOI: 10.3352/jeehp.2019.16.12
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the career preferences of medical students and interns: a cross-sectional, questionnaire-based survey from India

Abstract: Purpose: The study aimed to identify the motivational factors and demographic variables influencing the career preferences of medical students in India.Methods: We conducted a questionnaire-based survey at Christian Medical College, Vellore, India. The participants were 368 of the 460 medical students and interns enrolled at the institution from October 2015 to August 2016. We designed the questionnaire to collect demographic data, students’ preferences for career specialties, and the motivational factors infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 12 publications
2
26
0
4
Order By: Relevance
“…2015 [24] Sudan (NO) QT 647 First to fifth year 73.0% 38.6% NA 11 Average Alenezi M. 2019 [25] Saudi Arabia (NO) QT 75 Interns NA 52.0% 24.49 (2.15) 11 Average Alkhaneen H. 2018 [26] Saudi Arabia (NO) QT 436 Second and third phases 53.4% 57.0% NA 12 Average AlKhilaiwi RM. 2018 [27] Saudi Arabia (NO) QT 236 Fifth and final year 78.7% 64.8% NA 11 Average Alshahrani M. 2014 [28] Saudi Arabia (NO) QT 379 Fourth, fifth and sixth year 58.0% 33.3% NA 12 Average Alsubaie N. 2016 [29] Saudi Arabia (NO) QT 252 Second and third year 81.8% 50.4% NA 14 Good Anand R. 2019 [30] India (NO) QT 364 Bachelor 79.1% 37.9% NA 13 Good Anna Muscatello MR. 2017 [4] , [5] , [6] , [7] [31] USA (O) QT 335 Forth year 93.0% 52.9% ...…”
Section: Resultsmentioning
confidence: 99%
“…2015 [24] Sudan (NO) QT 647 First to fifth year 73.0% 38.6% NA 11 Average Alenezi M. 2019 [25] Saudi Arabia (NO) QT 75 Interns NA 52.0% 24.49 (2.15) 11 Average Alkhaneen H. 2018 [26] Saudi Arabia (NO) QT 436 Second and third phases 53.4% 57.0% NA 12 Average AlKhilaiwi RM. 2018 [27] Saudi Arabia (NO) QT 236 Fifth and final year 78.7% 64.8% NA 11 Average Alshahrani M. 2014 [28] Saudi Arabia (NO) QT 379 Fourth, fifth and sixth year 58.0% 33.3% NA 12 Average Alsubaie N. 2016 [29] Saudi Arabia (NO) QT 252 Second and third year 81.8% 50.4% NA 14 Good Anand R. 2019 [30] India (NO) QT 364 Bachelor 79.1% 37.9% NA 13 Good Anna Muscatello MR. 2017 [4] , [5] , [6] , [7] [31] USA (O) QT 335 Forth year 93.0% 52.9% ...…”
Section: Resultsmentioning
confidence: 99%
“…The students'sex may have been a determinant in specialty preference (29). Orthopedic surgery has been reported to be one of the least preferred subspecialties of surgery among female students, (30) despite reports indicating that the total number of female medical students undertaking OIPs has increased (20,30).…”
Section: Discussionmentioning
confidence: 99%
“…A-1-Controllable lifestyle: a large number of the studies (69%) reported that controllable lifestyle is an important determinant of specialty selection by MS. Controllable lifestyle is related to working hours [30,44,52], having enough personal or leisure time [23,33,47], and life stability (including quality of life, and enjoyable life) [38,48,49]. A-2-Economic concerns: economic and financial concerns are among the highly discussed factors (N: 20, 69%) regarding the choice of specialty.…”
Section: A-life Fulfillment Aspectsmentioning
confidence: 99%
“…Eighteen studies (62.1%) referred to this factor as a key determinant of specialty choice. Prestige [36,50], work safety [33,47], career features (including job satisfaction and climate of working environment) [44,45], as well as Specialty characteristics (including content of specialty, and extent of interaction with other specialties) [45,46] are four dimensions of this factor. B-2-Future working conditions: future working conditions are among the most frequent determinants of specialty selection (N: 17, 58.6%).…”
Section: B-influential Career Aspectsmentioning
confidence: 99%
See 1 more Smart Citation